2006
DOI: 10.1111/j.1537-2995.2006.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of surveillance methods for detection of bacterial contamination of platelets in a university hospital, 1991 through 2004

Abstract: Improved active surveillance methods for detecting PBC are needed to improve the safety of PLT transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 39 publications
3
123
1
4
Order By: Relevance
“…10 Culture was repeated on platelet specimens with initial positive culture results from samples retained at 4°C to determine whether results were true or false positives. True positives were defined as isolation of the same bacterial species from the repeat culture.…”
Section: Microbiology Methodsmentioning
confidence: 99%
“…10 Culture was repeated on platelet specimens with initial positive culture results from samples retained at 4°C to determine whether results were true or false positives. True positives were defined as isolation of the same bacterial species from the repeat culture.…”
Section: Microbiology Methodsmentioning
confidence: 99%
“…Assuming that the average hematology oncology patient may receive seven platelet concentrates during a 28-day period of support, the risk of exposure to a contaminated platelet concentrate is in the range of one in 150 per patient (Corash, 2011): "This level of risk would not be acceptable for other intravenous medications." Several studies (Yomtovian 2004;Yomtovian et al, 2006Yomtovian et al, , 2007 identified the major sources of contamination as donor skin and asymptomatic bacteremia. Less frequently, contamination of PRP may occur during processing or manufacture of blood collection devices (Blajchman et al, 2005).…”
Section: Iccvam Recommendations For Future Mat Validation Studies Maymentioning
confidence: 99%
“…Several studies on bacterial contamination of blood products have reported platelets as the most commonly contaminated blood product [3,5,6,[14][15][16]. In the United States, platelets accounted for the most common transfusion-associated infectious risk; they were reported to cause a 50-to 250-fold increase in the risk of transmission of HIV, HBV, and HCV [14].…”
Section: Introductionmentioning
confidence: 99%